Hubungan Kadar Albumin Plasma pada Penderita TB Mdr dengan Ko-Infeksi Hepatitis B - Farah Alfarisi; Fauna Herawati; Umi Fatmawati (Universitas Malahayati, 2026)
ABSTRACT Tuberculosis is a chronic infectious disease caused by the bacterium Mycobacterium tuberculosis. Resistance of the Mycobacterium tuberculosis (Mtb) germ is caused by spontaneous mutations in the chromosome. The proportion of Mtb germs that have undergone mutation (wild-type resistant mutants) in patients who have never received OAT is very small. TB treatment causes selective inhibition of the Mtb germ population, leading to the killing of sensitive Mtb germs, while the mutant population will reproduce and cause resistance to OAT (acquired resistance). A common co-infection in TB patients is Hepatitis B. Hepatitis B infection is a liver disease that causes inflammation and damage to hepatocytes. Chronic hepatitis B virus (HBV) infection in tuberculosis patients ranges from 0.5% to 44%. Hypoalbuminemia is often associated with both TB and Hepatitis B. It frequently occurs in hepatitis B due to liver damage caused by hepatitis B virus infection, while in TB, hypoalbuminemia is often linked to malnutrition and poor nutritional intake in TB patients. This hypothesis aligns with the patient's current condition, where the patient is diagnosed with hepatitis B confirmed by laboratory results showing HBsAg values 1000. Additionally, the patient also suffers from MDR TB with poor nutritional intake, as evidenced by the patient's BMI of only 19.53. Keywords: Hepatitis B, Hypoalbuminemia, Co-infection, Multi-drug resistant, Tuberculosis, Multi-Drug Resistant. ABSTRAK Tuberkulosis ada suatu penyakit kronik menular yang disebabkan oleh bakteri Mycobacterium tuberculosis. Resistansi kuman Mycobacterium tuberculosis (Mtb) disebabkan oleh mutasi spontan pada kromosom. Proporsi kuman Mtb yang sudah mengalami mutasi (wild-type resistant mutants) pada pasien yang tidak pernah mendapatkan OAT sangat sedikit. Pengobatan TB menyebabkan hambatan selektif pada populasi kuman Mtb sehingga kuman Mtb sensitif dibunuh, sementara populasi mutan akan bereproduksi dan menyebabkan terjadinya resistansi terhadap OAT (resistansi didapat). Ko-infeksi yang sering terjadi pada pasien TB adalah Hepatitis B. Infeksi hepatitis B adalah penyakit hati yang menyebabkan peradangan dan kerusakan hepatosit. Infeksi virus hepatitis B (HBV) kronis pada pasien tuberkulosis berkisar antara 0,5% hingga 44%. Hipoalbuminemia sering dikaitkan dengan penyakit TB maupun Hepatitis B. Pada hepatitis B sering terjadi dikarenakan adanya kerusakan hati yang disebabkan oleh infeksi virus hepatitis B, sedangkan pada TB sering terjadi hipoalbumin dikaitkan dengan malnutrisi dan kurangnya asupan gizi pada pasien TB. Hipotesis ini sesuai dengan kondisi pasien pada saat ini, dimana pasien didiagnosis hepatitis B yang ditegakkan dengan hasil pemeriksaan labortarorium dimana nilai HBsAg 1000, selain itu pasien juga menderita TB MDR dengan asupan gizi yang buruk, dimana dapat dilihat BMI pasien hanya 19.53. Kata Kunci: Hepatitis B, Hipoalbuminemia, Ko-Infeksi, Multi Drug Resistant, Tuberkulosis, Multi Drug Resistant.